Influenza A surface glycosylation and vaccine design - Wu, Chung-Yi; Lin, Chih-Wei; Tsai, Tsung-I; Lee, Chang-Chun David; Chuang, Hong-Yang; Chen, Jhih-Bin; Tsai, Ming-Hung; Chen, Bo-Rui; Lo, Pei-Wen; Liu, Chiu-Ping; Shivatare, Vidya S.; Wong, Chi-Huey (Proceedings of the National Academy of Sciences - PNAS, 2017)
We have shown that glycosylation of influenza A virus (IAV) hemagglutinin (HA), especially at position N-27, is crucial for HA folding and virus survival. However, it is not known whether the glycosylation of HA and the other two major IAV surface glycoproteins, neuraminidase (NA) and M2 ion channel, is essential for the replication of IAV. Here, we show that glycosylation of HA at N-142 modulates virus infectivity and host immune response. Glycosylation of NA in the stalk region affects its structure, activity, and specificity, thereby modulating virus release and virulence, and glycosylation at the catalytic domain affects its thermostability; however, glycosylation of M2 had no effect on its function. In addition, using IAV without the stalk and catalytic domains of NA as a live attenuated vaccine was shown to confer a strong IAV-specific CD8⁺ T-cell response and a strong cross-strain as well as cross-subtype protection against various virus strains.